Analisa Kerusakan Mesin Bubut Al Pin 350 Dengan Metode Failure Mode and Effect Analysis (FMEA) - Irfan Nurdiansah; Marno Marno; Aa Santosa (Peneliti.net, 2022)
The Manufacturing Industry is currently growing very rapidly, starting from systems, machines and other supporting equipment that make the current manufacturing industry very effective and efficient. maintenance plays an important role in maintaining the performance of the machines used in order to remain in optimal conditions, and there is no decrease in the quality of production results. The purpose of this study was to analyze the damage that occurred on the al pin 350 lathe at the Pusat Teknologi dan Keselamatan Reaktor Nuklir (PTKRN) workshop, the method to be used was Failure Mode and Effect Analysis (FMEA). During the inspection of all components from the spindle to the chuck, it was found that the Tailstock, Carriage, Toolpost, lighting and several components had problems. It is hoped that the data can be used as evaluation material for the company when it will carry out the maintenance process